„In erster Linie Arzt“ Erfahrungen hausärztlicher PJ-Lehrärzt:innen mit Medizindidaktik-Trainings - Hecht, Louisa; Roos, Marco; Sebastiao, Maria (Zeitschrift für Allgemeinmedizin, 2022)
Background Although participants evaluated Medical Didactic Courses (MDC) predominantly positively, there continues to be difficulties in the transfer of the learned training content into practice. The objective of the research was to identify reasons for this discrepancy by collecting the subjective experience of family medicine preceptors of the final year of medical studies (FMP). Methods In our qualitative study, we investigated personnel experience of 10 FMP’s with MDC though semi-structured interviews. The recorded interviews were transcripted by means of the software programme “f4” and subsequently coded in MAXQ-DA. Analysis of the data through content-structuring qualitative content analysis enabled the identification of complex relevance systems. Results In the interviews, the core experience identified was that the newly added teaching activity is competing with already exist-ing tasks in the daily routine of family medicine. The percep-tion of how deeply the teaching activity is naturally incorpor-ated within the medical profession of family doctors is quite ambivalent. The fear of additional workload stands in contrast to the benefit of working with the students. To facilitate a suc-cessful integration of the acquired skills into this complex work environment, a promotion of networking between FMP’s is re-peatedly proposed. Especially the reflection of the personal learning experiences within peers is regarded as supportive by the respondents. Accordingly this not only results in a strengthening of the teaching identity and therefore a better implementation of the training content, but also invokes a higher satisfaction in teaching. Conclusions To facilitate the implementation of the training content in a complex daily routine of family medicine, support of the FMP’s by increased networking in communities of practice is required.
CRIS-Team Scopus Importer:2022-11-25
Keywords: family medicine; general practice/education; physicians role; qualitative research; staff development/methods; teacher training